RELATIONSHIP OF THE SYNCHRONIZATION OF THE STRIKING ARM WITH THE RISING FOOT AND SOME KINEMATIC VARIABLES WITH THE ACCURACY OF THE JUMP SERVE IN VOLLEYBALL - Firas Chasib Khalaf, Mustafa Ismail Aseen, Zainab Abdulkadhim Hasnawi (Journals Park Publishing, 2023)
The importance of the serve level and its kinematic variables and the importance of the movement of the rising foot being synchronized with the movement of the striking arm were addressed. The correlation between the movement of the striking arm with the rising foot of and some kinematic variables of the stage of the jump serve. The research hypothesis was the existence of a positive correlation between the movement of the striking arm with the rising foot and some kinematic variables of the level of the serve, where the researchers used the descriptive approach to solve this problem and the research sample was the volleyball team of Misan Governorate for youth, as for the research tools, they were test and measurement, as the sample was tested, and after the completion of the main experiment, data were collected with special forms to be processed statistically through the use of appropriate statistical laws, and the results were presented, analyzed and discussed scientifically in the fourth chapter. The results were all moral. Depending on these results, conclusions were reached, including: (The movement synchronization between the striking arm and the rising foot has a positive effect on the accuracy of the serve), according to this, the researcher recommended the need to pay attention to these kinematic variables and the state of movement synchronization of the volleyball player.
Keywords: Striking Arm, Rising Foot, Accuracy, Jump, Volleyball.